Osteoporosis and its associated factors among patients attending Manakamana Hospital, Chitwan, Nepal. - Shankar Dhakal; Kalpana Sharma; Kishor Adhikari; Alisha Joshi; Sunita Poudyal (PLoS ONE, 2024)
Background Osteoporosis is the most common skeletal disorder that weakens bones and increases their susceptibility to fractures. It is becoming an urgent and serious global epidemic. Early diagnosis and treatment are essential to reduce morbidity and mortality associated with it. This study aimed to find out the prevalence of osteoporosis among patients attending at Manakamana Hospital, Bharatpur, Chitwan, Nepal. Methods A cross-sectional study was adopted and 623 patients attending at orthopaedic outpatients department (OPD) of Manakamana Hospital were selected using non-probability consecutive sampling technique. Data were collected from 15th October 2021 to 15th April, 2022, by using interview schedule, chart review and Bone Mineral Density (BMD) measurement through calcaneal ultrasonography. Ethical approval was obtained from Nepal Health Research Council Ethical Review Board prior to study procedures. Obtained data were analysed using descriptive statistics. Association between the variables were measured using chi-square test. Results The mean age of the patients was 43.5 (±14.26) years. Nearly half (44%, n = 274) were middle aged adults, 59.7% were female and 56.0% were involved in agriculture and household chores. Nearly half of the patients (45.7%) were overweight/ obese, 7.9% were smokers and 13.5% had habit of alcohol use. Osteopenia or low bone density was detected in 58.9% patients and 19.4% had osteoporosis. The prevalence of osteoporosis was significantly associated with age group (p = <0.001) and educational status (p = 0.013) of the patients. Conclusions and recommendations Osteoporosis and osteopenia are prevalent in patients attending in the hospital. Hence, awareness, early screening, and treatment are necessary for the hospital attended patients to enhance their health and, minimize the risk of osteoporosis and the consequences associated with it.